Coupled chemical reactions in dynamic nanometric confinement: VII. Biosensors based on swift heavy ion tracks with membranes. Issue 1 (1st February 2017) - Fink, D.; Muñoz H., G.; Garcia-Arrelano, H.; Alfonta, L.; Vacik, J.; Kiv, A.; Hnatowicz, V.
ABSTRACT: In previous papers it was shown that the coupling of the two chemical reactions: NaOH etchant – PET polymer and NaOH etchant – AgNO3 solution within the dynamic confinement of etched swift heavy ion tracks eventually leads to the formation of tiny Ag2 O membranes within these nanopores, thus separating the latter ones into two adjacent segments. It is shown here that the deposition of enzymes in these two segments transforms these structures into biosensors. In our earlier developed sensors with transparent etched ion tracks, we frequently used glucose oxidase as enzyme and glucose as analyte. In these cases, the enzymatic reaction within the tracks leads to a change in the pH value of the confined solution and hence also in the track conductivity, so these structures can be used for biosensing. When applying, for easy comparison, the same enzyme/analyte combination to the segmented sensor arrangement presented here, we find a striking improvement in detection sensitivity which points at a different biosensing mechanism due to intrinsic polarisation effects across the newly inserted membranes.